Ilmu Nafs: The Existence of The Application of Sufism to Human Psychological Conditions - Bakhtiar, Inayah Aqilah; Yusro, Ghefira Azzura Tazkiya; Azahro, Fatimah Nur (Proceedings of International Conference on Muslim Society and Thought, 2024)
The human soul is the fundamental component that builds a human being itself. The Soul serves as the source of consciousness, thoughts, and feelings, and is the true core element of a human being. The development of time raises various problematic aspects of life, such as social, economic, political, cultural customs, and so on. This complexity then envelops humans with different worldviews. Human assumptions about life can lead to inner struggles that potentially trigger mental complexities of the soul. Sufism plays a significant role in Ilmu Nafs, emphasizing a deep understanding of the human soul and its psychological conditions. The research aims to improve the existence of Sufism in human psychology by implementing Islam and faith in life. This research is a qualitative study based on the library research analytical method in writing. This research indicates a strong correlation between the science of Sufism and the sense of Self.